Drip and exudation irrigation effects of on vegetable yield in a cold climate - Benavides B., Orlando Edmundo; Barraza A., Fernando Vicente; Navia E., Jorge Fernando (Revista de Ciencias Agrícolas, 2017)
Small-scale vegetable crops South of Colombia. However, the increase in dry periods is threatening crop yields, therefore, pressurized irrigation have increased. This study aimed to compare the effect of drip and exudation irrigation systems and different crop cycles on lettuce (Lactuca sativa L.), cabbage (Brassica oleracea L. var. Capitata) and broccoli (Brassica oleracea L. var. Italica). We used the Randomized Complete Blocks design with bi-factorial treatment arrangements. The factor one, corresponds irrigation systems (drip irrigation, exuding hose systems and a control), meanwhile the factor two, comprised 2 planting seasons (the first, between September 9 and December 12 of 2013 and the second March 11 and June 13 of 2014). The drip irrigation system produced the greatest yield in all vegetables. For lettuce, a yield of 20t/ha was obtained, while a reduction of 13 and 18% was found for the control and exudation irrigation systems, respectively. For cabbage, yield was 53 t/ha and a decrease of 35% was observed for the control and exudation irrigation systems. For broccoli, 13t/ha were obtained, while the control and exudation system the yield was reduced by 59% and 40% respectively. Finally, the economic analysis showed that the control had the lowest cost/benefit relationship in all experiments.